Precoder design and node power allocation in multi-antenna amplify-and-forward (AF) relay systems - Danaee, Ahmad; Bahrami, Hamid Reza; Sadeghzadeh, Mehdi (2013 IEEE International Conference on Communications (ICC), 2013)
In this paper, the problem of precoder design and node power allocation in a three node cooperative multiple-input multiple-output (MIMO) relay system is discussed. All the nodes are assumed to be equipped with multiple antennas and the source and the relay nodes are subject to a total transmit power constraint. We first introduce an upper bound on the received mean square error (MSE), then we suggest suboptimal structures to the source and the relay precoders to minimize this bound. Unlike the previous works in this area, the proposed precoders are easy to calculate and does not involve in computationally costly iterative methods. Next, based on the precoder structures, it is shown that proper transmit power assignment to the source and relay nodes can further improve the system performance and the optimal power allocation for the special case of single symbol transmission is derived. Simulation results show significant improvement in the received mean square error (MSE) by applying the proposed precoding and node power allocation schemes. The node power allocation scheme is also shown to be most effective when the relay and destination nodes have different noise levels.